Mobile Cloud Computing Authentication: Methods and Techniques with Capabilities, Limitations - Shinde, Manjusha Anant; Ramesh, Jadhav Shradha (International Journal of Computer Sciences and Engineering, 2018)
Today the capabilities of mobile devices have improved real world user friendly applications, storage and feature support. The storage capacity can tremendously be increased with the use of cloud computing. Cloud computing is a flexible, cost effective and proven delivery platform for providing services. Mobile cloud computing means the availability of cloud computing services in a mobile environment. There are various authentication techniques being used like password, log off system, Biometric techniques. This process serves as a protection against different sorts of attacks where the goal is to confirm the identity of a user and the user requests services from cloud servers. Multiple authentication technologies have been put forward so far that confirm user identity before giving the permit to access resources. Authentication in cloud was fully explained in this paper together with the existing methods and the factors with its limitations.